Analysis of Kendari Mayor's Regulation Number 4 of 2015 on Waste Management: A CIPP Approach - Rina Ariani; Nurinti; Samsul; Histina (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Local Regulation Number 4 of 2015 on Waste Management was enacted by the Kendari City Government to address the increasingly complex waste management issues resulting from rapid urban population growth and expanding economic activity. This regulation aims to establish an efficient and sustainable waste management system through active participation from multiple sectors, including government agencies, the private sector, and local communities. A central focus is building cross-sectoral partnerships to promote not only waste reduction but also effective waste processing and reuse. Objectives: This study aims to evaluate the implementation of Local Regulation Number 4 of 2015 using the CIPP (Context, Input, Process, Product) model to determine the policy’s effectiveness and offer recommendations for improvement. Methods: A qualitative descriptive approach was used, involving analysis of regulatory documents and supporting literature. The CIPP evaluation framework was applied to assess the policy’s development and execution in a structured manner. Results: The regulation provides a comprehensive legal foundation for waste management, encompassing all key stages: sorting, collection, transportation, processing, and final disposal. However, implementation is hindered by limited infrastructure, low public awareness, and weak supervision and enforcement. Conclusion: Although the regulation has significant potential to improve environmental health in Kendari, its effectiveness depends on enhancing infrastructure, increasing community education, and strengthening coordination across sectors. Recommendations include infrastructure upgrades, awareness campaigns, and stricter enforcement of regulations. Keywords: Waste Management, Local Regulation, Policy Evaluation, CIPP Model, Environmental Governance